2020
DOI: 10.1063/1.5130680
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical electron transport in the cathode plume of a Hall effect thruster

Abstract: An experimental investigation is presented into the wave-driven electron transport in the near-field plume of a hollow cathode operating in a 300 V, 4.5 kW magnetically shielded Hall thruster. Correlational analysis of probe measurements in the cathode plume shows two types of electrostatic waves: ion acoustic turbulence propagating along the applied longitudinal magnetic field at frequencies from 500 to 1250 kHz and coherent, azimuthal anti-drift waves with a fundamental frequency of 95 kHz and mode numbers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Ref. [152]), which can be leveraged to relate transport coefficients such as an anomalous collision frequency to wave amplitude and growth rate. Ideally, this method requires simultaneous measurements of the electric field and density fluctuations associated with the waves.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [152]), which can be leveraged to relate transport coefficients such as an anomalous collision frequency to wave amplitude and growth rate. Ideally, this method requires simultaneous measurements of the electric field and density fluctuations associated with the waves.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 99%
“…13 (b), illustrates how these MHz fluctuations exhibit an additional kHz range modulation (measurable due to the fluctuations in density as spokes traverse the measurement region). Recent experimental work on hollow cathodes operating in conjunction with a Hall thruster also showed that not only does plasma turbulence dominate the electron transport in the cathode, but it also may be linked to lower-frequency oscillations [151], [152]. Taken together, these experimental results from cathodes, Hall thrusters, and magnetrons now point to the conclusion that turbulence-driven transport has a critical role in governing both the steadystate plasma properties as well as the transient, large scale oscillations discussed in Sec.…”
Section: State Of the Art And Recent Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of the IAT to the total electron collision frequency can be estimated by the anomalous collision frequency, ν IAT an . Assuming that in an experimental context ñe / n e ≈ Ĩsat /I sat,0 [32], where I sat is the ion saturation current collected by the probe with its mean value I sat,0 , the anomalous collision frequency has the following expression [30]:…”
Section: Governing Equations For Cathode Plume Electron Transport And...mentioning
confidence: 99%
“…Anomalous electron transport has been strongly linked to plasma oscillations in HTs [5] in both the thruster discharge channel [6,7] and cathode regions [8]. Long-wavelength azimuthal oscillations, the focus of this work, are typically characterized in a Fourier representation with integer mode numbers, m, including the azimuthally uniform m = 0 "breathing" modes in HT channels [9,10] and cathodes [11,12], m > 0 azimuthally rotating "spoke" modes in the channel, and a m = 1 counter rotating "antidrift" modes around the cathode [13].…”
Section: Introductionmentioning
confidence: 99%